51.5k views
0 votes
Which expression is NOT equivalent to the other three?

-9 - 7n + 16n

9(n - 9)

n - 9 + 8n

9n - 9

User Dader
by
6.1k points

2 Answers

1 vote

Answer-9(n - 9) = 9n - 81

Explanation:

"Equivalent expressions are expressions which are equal . To determine if expressions are equivalent, simplify to lowest terms through combining like terms."

-9 - 7n + 16n = -9 + 9n-equivalent

9(n - 9) = 9n - 81 -not equivalent

n - 9 + 8n = -9 + 9n-equivalent

9n - 9 = -9 + 9n-equivalent

User Ylor
by
4.9k points
5 votes

Answer:

9(n - 9) = 9n - 81

Explanation:

Equivalent expressions are expressions which are equal . To determine if expressions are equivalent, simplify to lowest terms through combining like terms.

-9 - 7n + 16n = -9 + 9n

9(n - 9) = 9n - 81

n - 9 + 8n = -9 + 9n

9n - 9 = -9 + 9n

User Ramkumar Hariharan
by
4.9k points